2019
DOI: 10.1155/2019/4873870
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Licania macrocarpa Cuatrec Methanol Extract Target Src- and TAK1-Mediated Pathways

Abstract: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…B16F10 cells were treated with TSA (12.5–25 µM) or arbutin (1 mM) with μ-MSH (100 nM) for 48 h. We prepared the total cell lysates, as previously described [ 62 , 63 ]. Cells (1 × 10 6 cells/mL) were washed with cold PBS and lysed with buffer (20 mM Tris-HCl, pH 7.4, 2 mM EDTA, 2 mM EGTA, 50 mM glycerol phosphate, 1 mM DTT, 2 µg/mL aprotinin, 2 µg/mL leupeptin, 1 µg/mL pepstatin, 50 µM PMSF, 1 mM benzamide, 2% Triton X-100, 10% glycerol, 0.1 mM sodium vanadate, 1.6 mM pervanadate, and 20 mM NaF).…”
Section: Methodsmentioning
confidence: 99%
“…B16F10 cells were treated with TSA (12.5–25 µM) or arbutin (1 mM) with μ-MSH (100 nM) for 48 h. We prepared the total cell lysates, as previously described [ 62 , 63 ]. Cells (1 × 10 6 cells/mL) were washed with cold PBS and lysed with buffer (20 mM Tris-HCl, pH 7.4, 2 mM EDTA, 2 mM EGTA, 50 mM glycerol phosphate, 1 mM DTT, 2 µg/mL aprotinin, 2 µg/mL leupeptin, 1 µg/mL pepstatin, 50 µM PMSF, 1 mM benzamide, 2% Triton X-100, 10% glycerol, 0.1 mM sodium vanadate, 1.6 mM pervanadate, and 20 mM NaF).…”
Section: Methodsmentioning
confidence: 99%
“…Upon stimulation, TAK1 could activate the MAPKKs (MKK3/6 and MKK4/7) to transduce the signal to MAPKs (p38, JNK, and ERK) [ 23 ], although this protein is also involved in the activation of the NF-κB pathway. In addition, anti-inflammatory remedies derived from compounds or plant extracts that target TAK1 have been reported to inhibit inflammatory responses via a blockade of AP-1 pathways [ 24 , 25 , 26 ]. Using overexpression strategies and CETSA assays, we confirmed that Src and TAK1 were targeted by Cs-EE as well as gained insight into the interaction of Cs-EE with its target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Using overexpression strategies and CETSA assays, we confirmed that Src and TAK1 were targeted by Cs-EE as well as gained insight into the interaction of Cs-EE with its target proteins. Following previous studies, Src- or TAK1-overexpressing HEK293 cells expressed autophosphorylation events of Src and TAK1, respectively [ 24 , 26 ]. Treatment with Cs-EE reduced protein expression of phosphorylated Src and TAK1 as well as led to the thermo-stabilization of Src and TAK1.…”
Section: Discussionmentioning
confidence: 99%
“…We then conducted further experiments to further study the functional mechanism of AccMKK4. Yeast two‐hybrid interaction experiments showed that AccMKK4 interacts with Accp38b, and similar results were also obtained in some recent studies (Li et al ., 2018b, Wang et al ., 2018; Shin et al ., 2019). Subsequently, we successfully silenced the AccMKK4 gene, and after the silencing of AccMKK4 , we detected the expression level of Accp38b and found that the expression level of Accp38b was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%